Cymbidium codonanthum (Orchidaceae; Epidendroideae; Cymbidiinae), a new species from China: evidence from morphological and molecular analyses - Jiang, Yuting; Ma, Liang; Lin, Ruqiang; Xiong, Yuanfang; Jiang, Shuzhen; Liu, Bin; Liu, Zhong-Jian; Chen, Shipin (Phytotaxa, 2020)
A new orchid species, Cymbidium codonanthum, from Yunnan Province, China, is described and illustrated based on morphological and molecular analyses. A detailed comparison between the newly discovered orchid and other members of Cymbidium was performed. The new plant what is similar to C. cochleare, but it is characterized by several morphological features that distinguish it from the latter as well as all other known species of Cymbidium. A molecular study based on nuclear ribosomal ITS and plastid matK and rbcL DNA sequence data indicates that C. codonanthum is genetically distinct from other species and a member of Cymbidium section Cyperochis.